MONTE CARLO STUDY OF Ar+ INDUCED KINETIC ELECTRON EMISSION FROM MgO THIN FILM - Ullah, Shakir; Dogar, A. H.; Qayyum, A. (The Nucleus, 2010)
A Monte Carlo program has been developed to investigate the electron emission from 5000 Ã… thick MgO film for impact of Ar + ions having energies in the range of 50 to 1000 eV. The program incorporates the excitation of target electrons by projectile ions, recoiling target atoms and fast primary electrons. It can be used to calculate the kinetic electron yield, distribution of the electron excitation points in the solid and other physical parameters of the emitted electrons. The calculated electron emission yield is compared with the available experimental data, considering the effect of potential emission a good agreement is found. In addition, the effect of projectile energy and incident angle on the longitudinal distribution of the excitation points of electrons emitted from MgO thin film is investigated. PACS: 79.20.Rf; 79.20.Rf